Hydrogen‐bonded and π‐interaction assembly in two 8‐alkoxycarbonyl‐1, 8‐diazabicyclo[5.4.0]undec‐7‐enium chloride salts. (13th March 2013) - Mesto, E.; Quaranta, E.
<x xml:space="preserve">Abstract</x> The crystal structures of 8‐phenoxycarbonyl‐1, 8‐diazabicyclo[5.4.0]undec‐7‐enium chloride, C16H21N2O2+·Cl−, (I), and 8‐methoxycarbonyl‐1, 8‐diazabicyclo[5.4.0]undec‐7‐enium chloride monohydrate, C11H19N2O2+·Cl−·H2O, (II), recently reported by Carafa, Mesto & Quaranta [Eur. J. Org. Chem. (2011), pp. 2458–2465], are analysed and discussed with a focus on crystal interaction assembly. Both compounds crystallize in the space group P21/c. The crystal packings are characterized by dimers linked through π–π stacking interactions and intermolecular nonclassical hydrogen bonds, respectively. Additional intermolecular C—H...Cl interactions [in (I) and (II)] and classical O—H...Cl hydrogen bonds [in (II)] are also evident and contribute to generating three‐dimensional hydrogen‐bonded networks.